WASTE GENERATION MODELING BASED ON SOCIOECONOMIC AND SOCIODEMOGRAPHIC FACTORS IN WEST JAVA USING GEOGRAPHICALLY WEIGHTED REGRESSION - Sri Pingit Wulandari; Sri Mumpuni Retnaningsih; Nimas Ayu Prabawani; Apsarini Pradipta (Department Statistics, Faculty Mathematics and Natural Science, UNIMUS, 2025)
Waste has become a national concern, reflecting the increasing consumption patterns within society. The rise in consumption contributes to the growing volume and diversity of waste generated. This issue is also aligned with Sustainable Development Goals (SDGs) Goal 12, which emphasises responsible consumption and production. West Java Province is one of the provinces with the highest total waste generation in Indonesia. Several factors likely influence the annual increase in waste generation in West Java. Therefore, this study aims to model the factors affecting waste generation in West Java Province by incorporating spatial aspects using the Geographically Weighted Regression (GWR) method. Based on the analysis, the GWR model was applied using an adaptive bisquare kernel function, achieving a model fit of 96.65%. The factors found to have a significant influence on waste generation in West Java Province include life expectancy of schooling (HLS), the percentage of the population living in poverty, and the Gross Regional Domestic Product (GRDP) at constant prices.